Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

Follow the trail of responses and if you have anything to add please sign up or sign in.

You can ask your own question or look at similar Maths questions.

So to solve (3x-4) = (4x-3)2 the first thing I would do is expand the brackets / multiply the brackets on the right hand side of the equation which would give us:

3x-4 = 8x - 6

The next thing i would do is bring the x’s on one side and the numbers on the other. So in this case I will bring the 3x over to the right side by misusing 3x on both sides, and I will bring the 6 over to the left side by adding 6 on both sides, which would give us:

2 = 5x

To find x we can the divide both sides by 5 which would give us:

X = 2/5

(3x-4)=(4x-3).2 

3x-4=8x-6

3x-8x=-6+4

-5x=-2

x=-2/(-5)

x=2/5 

you need to change the signs when to put the numbers on the other side.

the opposite of + is - and the opposite of multiplication is division.

multiplying the brackets on the right side we get:

3x-4=8x-6

We have to try to bring x to one side and numbers to the other. So we add 6 both sides. We get:

3x+2=8x

Now we have to minus 3x.

2=5x

now we need to divide by 5, to get x, therefore x is:

x=2/5


3x-4=8x-6

-4=5x-6

2=5x

2/5=x

(3x - 4) = (4x - 3) 2 

3x - 4 = 2*4x - 2*3 

3x - 4 = 8x - 6

6 - 4 = 8x - 3x

2 = 5x 

x = 2/5

(3x-4)=(4x-3)2

3x-4=8x-6

3x-8x=-6+4

-5x=-2

x=2/5

When getting such questions, always expand the brackets first. Then move all x to one side of the equation

(3x-4)=(4x-3)2

Step one: 3x-4=8x-6

Step two: 2=5x

x=2/5

3x-4 = (4x - 3 ) 2

=> 3x-4 = (4x - 3 ) * 2

=> 3x-4 = ( 4x * 2 )  -  ( 3  * 2 )

=> 3x-4 = 8x - 6

=> 3x- 8x = 4-6

=> -5x = -2

=> 5x = 2

=> x = 2/5

Footer Graphic